Estudo das alterações morohistológicas em larvas de Aedes aegypti submetidas ao tanino catéquino isolado da Magonia pubescene (Sapindaceae) e ao diterpeno de Copaifera reticulata(Leguminosae) - VALOTTO, Cleyde Ferreira Barreto (2009)
The dengue and yellow fever are caused by Flavivirus, and are an importants problems in public health in the range of tropical and subtropical world. There is only available vaccine for yellow fever. The transmission of both diseases to humans is by the bite of female Aedes aegypti. The vector control is done through the elimination of breeding potential, application of larvicides in collections of water for adults vectors space applications of insecticides. The problems arising from continuous use of chemical insecticides have been the emergence of resistant populations to these products and concern about the environmental damage caused by slow degradation. In search of alternatives for the vector control, studies are being developed with substances of botanical origin, with the aim to control the vectors and preserve the environment. The use of natural insecticides has some advantages when compared to synthetic because they are renewable and have rapid degradation. Moreover, its composition is quite complex, reducing the speed of emergence of resistance and be of low toxicity to mammals, birds and environment. This study presents the morphohistologic and ultrastructural changes of catechist tannin extracted from Magonia pubescens, and the Diterpene extracted from Copaifera reticulata on the larvae of A. aegypti with the objective to evidence the mechanisms of action of these substances. For light microscopy, the 3rd stage larvae were subjected to a solution of catechist tannin 37ppm and the diterpene 9ppm, where they remained for up to 24h. Larvae that reached lethargic state were collected and fixed in 4% in the paraformoldehyde buffer 0.1 M sodium cacodilate pH 7.2, included in resin and the slides stained with hematoxylineosin technique. For electron microscopy, larvae were subjected to the same concentrations of catechist tannin and diterpene, where they remained for 22 h. Larvae that reached lethargic state were collected and dissected and their gut fixed in 2% glutaraldehyde, 2% paraformoldehyde, 3% sucrose in sodium buffer cacodilate 0.1 M pH 7.2 and post fixed in osmium tetroxide at 1% in cacodilate sodium 0.1 M. After this they were contrasted with uranyl acetate 1%, dehydrated, embedded and polymerized. The ultra sections were contrasted with uranyl acetate 3% and lead citrate and were caracterized by eletron microscopy. The changes caused by catechist tannin observed by light 20 and electron microscopy were high vacuolation, absence of cytoplasmic limits, cellular aging, cell disruption, vesicular apical formation with release of cytoplasmic content, increase in intercellular spaces, detachment of cells from the basal lamina and structural change of microvilli. Changes by diterpene by light and electron microscopy were high cytoplasmic vacuolation, cells and nuclei hypertrophy, degeneration of the edge brush, vesicular apical formation with release of cytoplasmic contents of cells, stratification of the epithelium and folds in the peritrophic matrix.